Knowledge, attitude and practice of parents towards antibiotic usage and its resistance - Chinnasami, Balaji; Sadasivam, Kanimozhi; Ramraj, Balaji; Pasupathy, Sekar (International Journal of Contemporary Pediatrics, 2016)
Background: To assess the knowledge, attitude and practices about rational antibiotic usage and antibiotic resistance among parents attending a hospital based setting in Tamilnadu. Methods: The study was a cross-sectional quantitative study in which four hundred and ninety one respondents, majority of them aged 20-50 years participated. A standard questionnaire comprising of questions related to antibiotics, its indications, resistance and doctor-patient relationship was given to them and their responses were recorded. Results: Majority of participants were young and educated parents. Most of them were not aware of the indications of antibiotics with only 17% agreeing that antibiotics have no role against viruses. Also only 20% accepted that antibiotics are not necessary for short duration fever and common cold. Around 60% are of the opinion that full course of antibiotics should be completed and left over antibiotics should not be saved for later use. Participants with prior medical training had 18 times better knowledge about antibiotics as compared to general public. There was no significant association between antibiotic prescription patterns and trust over doctors. Conclusions: Majority of participants’ knowledge as well as attitude towards rational antibiotic usage is less and educational programs for public to combat antibiotic resistance should address both these issues. The high level of trust on doctors by parents should encourage physicians to be rational in their antibiotic prescriptions.